PANDUAN BIMBINGAN INTERAKSI SOSIAL BERBASIS KECERDASAN INTERPERSONAL UNTUK PESERTA DIDIK SMP - Nisa, Athia Tamyizatun; Wagimin, Wagimin; Djannah, Wardatul (Universitas Sebelas Maret, 2015)
The purpose of this research is to create a product of the direction of social interaction guidance based on interpersonal intelligence for junior high school students which had been validated according to the experts and practices. This is a research and development research which is adapted from Borg and Gall concept. The result of validation test shows the average score which is got from the experts and practices with the amount 82.1 percent. Based on the validity criteria table, the score could be included to the valid enough criteria, or could be used with small revision. It means, the product of the direction of social interaction guidance based on interpersonal intelligence is proper to be used but with small revision. The revision is done based on the proposition from the experts and the practices. According to this research, it could be concluded that the direction of social interaction guidance based on interpersonal intelligence is valid based on the experts and the practices.